Knowledge and Practices of Jordanian Nurses on Needlestick Injuries. Issue 1 (January 2015) - Abozead, Shalabia El-Sayead; Abuhasheesh, Mohammad; Nawafleh, Hani; Kawafha, Mariam M.; Al-Tarawneh, Omar
<x xml:space="preserve">Abstract</x> Background Healthcare workers are exposed to a range of factors related to diseases as well as infectious organisms. They are also exposed to needlestick injuries (NSIs) due to a lack of common and uncertain reporting system. The NSIs are a potential hazard for healthcare workers that were recognized as a serious risk factor for transmitting diseases by exposure to needlesticks contaminated with blood-borne pathogens. Aim The aim of the present study was to determine the frequency and occurrence of NSIs and determinants in nursing care in selected hospitals in Jordan. Methods This study used a cross-sectional design. It was conducted in 2 types of Jordanian hospitals: governmental and private. A total of 210 Jordanian nurses were recruited to participate in the study. Data were collected using a questionnaire that included demographic variables, NSIs during work, and causes. Results Results showed that the mean (SD) age of participants was 32.4 (7.21) years. Approximately 67% of the participants had less than 5 years of experience. Most of the participants (75.5%) had an NSI. Sixty-one percent did not attend any training program about infection control; 12.2% had a positive immune status (Hepatitis B surface antigen, anti-Hepatitis C virus, and anti-human immunodeficiency virus), and 48% did not know it. More than half of the injuries (53%) to nurses occurred during recapping of a needle. Forty-seven percent of injured nurses did not report the injury to anyone. Approximately half of the nurses (48%) did not report (NSIs) to anyone, do not want to admit NSI to a supervisor, and were not concerned about NSI either. Conclusions The frequency of NSIs among nursing care workers is high, and reporting is low. It needs to be further investigated. Special interventions such as in-service training of nurses on infection control measures, standardized treatment after exposure, and follow-up are necessary.